The Potential of Islamic Boarding Schools and Their Effort of Development and Fostering at Pesantren Persatuan Islam 1-2 Bandung) - Aziz, Asep Abdul; Budiyanti, Nurti; Ahmad, Nurwadjah; Suhartini, Andewi (Graduate Program Magister Manajemen Pendidikan, 2021)
The existence of boarding schools in Indonesia, in its development and coaching was very influential to the surrounding community, especially in terms of education. The world education was now facing a case of moral degradation great increasingly. The presence of Pesantren educational institutions can certainly strengthen Islamic civilization. The researchers used qualitative approach with case study methods at Pesantren Persatuan Islam 1-2 Bandung. The results of the study showed that Pesantren Persatuan Islam 1-2 Bandung was one of the modern pesantren that combines religious science and general science. Pesantren has the potential to give birth to students who are independent, sincere, tolerant, simple, and can establish a good ukhuwah ilsmaiyaah. The result has proven from the coaching program that was done either at KBM hours or outside KBM. The effort construction carried out in outside the KBM were ikhtifal activities, bai'at activities, hadith research activities, tahsin wa tahfidz halaqah activities, as well as Arabic language worship activities. While the efforts construction on KBM were adjusted in existing subjects both containing the general curriculum of IPA and IPS programs, the central religious curriculum (akidah akhlak, al-quran, Islamic cultural history, and fiqh), as well as pesantren curriculum such as balaghah, mantiq, maani, hiwar, ushul fiqh, tafsir ahkam, fafsir aam, aqidah, nahwu sharaf, and falaq science). All subjects are directed to embody a generation that is tafaquh fid-in.Â Keyword: The Potential Islamic Boarding School; Development Pesantren, Fostering Pesantren